# Difference between revisions of "Nabla derivative"

(→Properties of the $\nabla$-derivative) |
(→Properties of the $\nabla$-derivative) |
||

Line 6: | Line 6: | ||

==Properties of the $\nabla$-derivative== | ==Properties of the $\nabla$-derivative== | ||

− | + | [[Nabla differentiable implies continuous]]<br /> | |

− | |||

− | |||

− | |||

− | |||

− | |||

− | </ | ||

<div class="toccolours mw-collapsible mw-collapsed" style="width:800px"> | <div class="toccolours mw-collapsible mw-collapsed" style="width:800px"> |

## Revision as of 00:53, 23 August 2016

Let $\mathbb{T}$ be a time scale. If $\mathbb{T}$ has a right-scattered minimum $m$, then define $\mathbb{T}_{\kappa}=\mathbb{T} \setminus \{m\}$, otherwise let $\mathbb{T}_{\kappa}=\mathbb{T}$. Define the backward graininess function $\nu \colon \mathbb{T}_{\kappa} \rightarrow \mathbb{R}$ by $$\nu(t) = t - \rho(t).$$

Let $f \colon \mathbb{T} \rightarrow \mathbb{R}$ and let $t \in \mathbb{T}_{\kappa}$. The $\nabla$-derivative of $f$ at $t$ is denoted by $f^{\nabla}(t)$ to be the number such that given any $\epsilon > 0$ there is a neighborhood $U$ of $t$ and $s \in U$, $$|f(\rho(t))-f(s)-f^{\nabla}(t)[\rho(t)-s]|\leq \epsilon|\rho(t)-s|.$$

## Contents

## Properties of the $\nabla$-derivative

Nabla differentiable implies continuous

**Theorem:** If $f$ is continuous at $t$ and $t$ is left-scattered, then
$$f^{\nabla}(t) = \dfrac{f(t)-f(\rho(t))}{\nu(t)}.$$

**Proof:** █

**Theorem:** If $t$ is left-dense, then (if it exists),
$$f^{\nabla}(t) = \lim_{s \rightarrow t}\dfrac{f(t)-f(s)}{t-s}.$$

**Proof:** █

**Theorem:** If $f$ is differentiable at $t$, then
$$f(\rho(t))=f(t)+\nu(t)f^{\nabla}(t).$$

**Proof:** █

**Theorem (Sum rule):**
$$(f+g)^{\nabla}(t)=f^{\nabla}(t)+g^{\nabla}(t).$$

**Proof:** █

**Theorem (Constant rule):** If $\alpha$ is constant with respect to $t$, then
$$(\alpha f)^{\nabla}(t) = \alpha f^{\nabla}(t).$$

**Proof:** █

**Theorem (Product rule,I):** The following formula holds:
$$(fg)^{\nabla}(t)=f^{\nabla}(t)g(t)+f(\rho(t))g^{\nabla}(t)).$$

**Proof:** █

**Theorem (Product rule,II):** The following formula holds:
$$(fg)^{\nabla}(t) = f(t)g^{\nabla}(t)+ f^{\nabla}(t)g(\rho(t)).$$

**Proof:** █

**Theorem (Quotient rule):** The following formula holds:
$$\left( \dfrac{f}{g} \right)^{\nabla}(t) = \dfrac{f^{\nabla}(t)g(t)-f(t)g^{\nabla}(t)}{g(t)g(\rho(t))}.$$

**Proof:** █

## Theorem

Let $\mathbb{T}$ be a time scale and let $f \colon \mathbb{T} \rightarrow \mathbb{R}$. If $f$ is $\Delta$-differentiable and $f^{\Delta}$ is rd continous on $\mathbb{T}^{\kappa}$, then $f$ is **$\nabla$-differentiable** on $\mathbb{T}_{\kappa}$ and
$$f^{\nabla}(t) = f^{\Delta}(\rho(t)).$$

## Proof

## References

## Theorem

Let $\mathbb{T}$ be a time scale and let $f \colon \mathbb{T} \rightarrow \mathbb{R}$. If $f$ is **$\nabla$-differentiable** on $\mathbb{T}_{\kappa}$ and $g^{\nabla}$ is ld continuous on $\mathbb{T}_{\kappa}$, then $f$ is $\Delta$-differentiable on $\mathbb{T}^{\kappa}$ and
$$g^{\Delta}(t) = g^{\nabla}(\sigma(t)).$$

## Proof

## References

# References

Nabla dynamic equations on time scales - D. Anderson, J. Bullock, L. Erbe, A. Peterson, H. Tran